Clustering of Acute and Subacute Stent Thrombosis Related to the Introduction of Generic Clopidogrel. (March 2014) - Kovacic, Jason C.; Mehran, Roxana; Sweeny, Joseph; Li, Jennifer R.; Moreno, Pedro; Baber, Usman; Krishnan, Prakash; Badimon, Juan J.; Hulot, Jean-Sebastien; Kini, Annapoorna; Sharma, Samin K.
Introduction: Generic clopidogrel recently became available in the United States and was rapidly adopted as a cost-effective alternative to the brand name formulation. However, unlike other medications, subtle differences in clopidogrel bioavailability may lead to acute consequences including stent thrombosis (ST). Materials and Methods: We studied the incidence of acute and subacute ST during the initial period of generic clopidogrel use (June 18, 2012-September 6, 2012 [80 days]) at a single percutaneous coronary intervention (PCI) center. There were 4 definite ST cases within 30 days of successful PCI in patients receiving generic clopidogrel, which were compared to historic control ST cases from 80 days prior to generic clopidogrel use and for 3 years from June 18, 2009 to June 17, 2012. Results: During generic clopidogrel administration, 1054 PCIs were performed, giving a definite 30-day ST incidence of 0.38% (4 of 1054) among these patients. By comparison, there were 2 episodes of definite 30-day ST during the 80 days immediately preceding generic clopidogrel use (2 of 1114), while 3-year historic data indicated a definite 30-day ST incidence of 0.14% (20 of 14 432), representing a 2.7-fold increase in definite 30-day ST with generic clopidogrel use ( P = .076). Exclusion of 3 historic controls with a defined reason for ST (noncompliance, marked thrombocytosis) gave a 3.2-fold increase in 30-day ST with generic clopidogrel ( P = .050). An ST-predictive algorithm revealed no difference in the likelihood of ST between patients receiving generic clopidogrel and historic controls. Conclusions: We observed an unexpected >2-fold increase in ST coincident with generic clopidogrel use. Although we cannot ascribe causality, this observation warrants increased vigilance and close monitoring of patients receiving generic clopidogrel.